2004
DOI: 10.1021/ma049930j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Functionalized Monodisperse Poly(methyl methacrylate) Nanoparticles by a RAFT Agent Carrying Carboxyl End Group

Abstract: A RAFT agent bearing a carboxylic acid group is applied to the miniemulsion polymerization of methyl methacrylate (MMA) in order to prepare the stability-enhanced functionalized latex. At the polymerization temperatures of 60, 70, and 80 °C, the polymerization kinetics, evaluation of the molecular weight, and PDI are found to be strongly dependent on the temperature. The higher the temperature, the faster the polymerization rate, the lower the molecular weight, and the lower the PDI are obtained. The PMMA nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 48 publications
0
50
0
1
Order By: Relevance
“…[9,68,82,102,[185][186][187][188][189][190][191][192][193][194][195] We showed that RAFT in miniemulsion can be used to produce polystyrene of narrow polydispersity in a batch process. [9] Some retardation is observed with dithiobenzoate RAFT agents.…”
Section: Raft In Heterogeneous Mediamentioning
confidence: 99%
“…[9,68,82,102,[185][186][187][188][189][190][191][192][193][194][195] We showed that RAFT in miniemulsion can be used to produce polystyrene of narrow polydispersity in a batch process. [9] Some retardation is observed with dithiobenzoate RAFT agents.…”
Section: Raft In Heterogeneous Mediamentioning
confidence: 99%
“…A Tabela 1 apresenta os estudos publicados até a presente data sobre a produção de polímeros que utilizaram a técnica RAFT em miniemulsão. Conforme revisado, a técnica de polimerização RAFT em miniemulsão já foi adaptada para os principais tipos de monômeros comerciais (como, por exemplo, estireno [28,34,35, , metacrilato de metila [35,54,68,[74][75][76][77][78][79][80] ), sistemas inversos [23,52,[81][82][83][84][85][86] e sistemas contínuos de polimerização [87][88][89] ). Além dos trabalhos citados na P(AM-co-AA) Inverso [83] P(NIPAM-b-PEO) Inverso [82] a Poliestireno (PSt), poli(metacrilato de metila) (PMMA), poli(buitl metacrilato (PnBMA), poli(hidroxietil metacrilato) (PEHMA), poli(butil acrilato) (PnBA), poli(acetato de vinila) (PVAc), Poliacrilamida (PAM), poli(ácido acrílico), poli(2-dimetilamino (metacrilato de etila)) (PDMAEMA), ácido metacrílico (MAA), acrilato de dodecafluoro heptil (DFHA), acrilamida (AM), ácido acrílico (AA), isopopil acrilamida (NIPAM), poli(óxido de etileno) (PEO).…”
Section: Polimerização Raft Em Miniemulsãounclassified
“…RAFT miniemulsion polymerization has been recently reviewed by Zetterlund and co-workers [10] and by Cunningham [7]. In addition, numerous papers have appeared reporting on the RAFT miniemulsion of a large range of monomers such as: styrene [126][127][128][129][130][131][132][133][134] [ [135][136][137][138][139][140][141][142][143][144],4-acetoxystyrene [145],MMA [135,138,142,[146][147][148],EHMA [129,136], nBMA [129,136,147,[149][150][151], nBA [127,128,141,152,153], MAA [153], fluorinated alkyl methacrylates [149,151], acrylamide (inverse RAFT miniemulsion) [125], VAc [154,…”
Section: Reversible Addition-fragmentation Chain Transfer Miniemulsiomentioning
confidence: 99%
“…polymerizable surfactants) [142,164] or functionalized RAFT agent can be used. In particular, carboxylic acid functionalized PS [137] or PMMA [146] particles exhibit a better stability due to the presence of ionizable carboxylic acid groups (coming from the RAFT agent) at the surface of particles, hence increasing the electrostatic stabilization.…”
Section: Colloidal Instabilitymentioning
confidence: 99%